Spin modes in electron Fermi liquid of organic conductors - Peschansky, V.G.; Stepanenko, D.I. (Физика низких температур, 2007)
The propagation of spin waves in Q2D layered conductors placed in a magnetic field is studied. It is
shown, that at certain orientations of the magnetic field with respect to the layers the collisionless absorption
is absent and weakly damping spin waves can propagate even under the strong spatial dispersion. We
have analyzed the spectrum of spin modes at an arbitrary form of Landau–Silin correlation function.